EFEKTIFITAS PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP MOTIVASI DAN HASIL BELAJAR MENGIDENTIFIKASI UNSUR-UNSUR CERITA ANAK DI KELAS V SD NEGERI 018 KUBANG JAYA KECAMATAN SIAK HULU - Yusmarwati Yusmarwati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research is based on low student learning outcomes and motivation in learning. Research was conductedon grade V students of SD Negeri 018 Kubang Jaya, Siak Hulu, Kampar. This research aims to improve studentlearning outcomes and motivation through audio visual media. From data analysis result of observation ofactivity of teacher in learning using audio visual at meeting of petarma get percentage sebear 89,5%. at thesecond meeting of 95,83%. while the results of observations of student activities first meeting students get apercentage of 89,29%. while at the second meeting 96,43%. seen from the analysis of student motivation dataexperimental class high libih motivation in learning from the control class. Furthermore, in terms of studentlearning outcomes seen from the basic scores of students who are in class experiments get an average score of58.86, while the control class gets an average score of 60,68. After the students were given an experiment in theexperimental class, the average grade increased to 80,00, while the value in the control class that was not giventhe treatment received an average score of 69.55. From the analysis of the data, it can be concluded that theaudio visual media applied to the learning process is very effective, this is evidenced by the increasingmotivation and student learning outcomes in class V Elementary School 018 Kubang Jaya Kubang Jaya, SiakHulu, Kampar.